Bem-estar no trabalho: impacto das políticas de gestão de pessoas e o papel mediador da justiça nas organizações em uma instituição pública - Sampaio, Thania Acciari (2015)
Work is extremely important to person s life, contributing to his/her survival and adjustment to the world. Well-being at work (WBW) is an essential phenomenon to a suitable and competitive organization performance considering that perceptions of WBW can generate consequences in the own employee s life quality, as in the organizational productivity. WBW can be defined as the person s satisfaction of necessities and fulfillment of desires while playing his/her role in the organization. This study investigate the impact of the perception of policies and practices of people management (HRMPP), when mediated by perception of justice in the organizations (OJ) in the reports of BET of 83 psychologists (n=83) of a City hall in Triângulo Mineiro. The research hasn t confirmed the theoretical model, demonstrating demonstrated that HRMPP, in personal perception of involvement, explained 52% of the model, while the dimension of justice in the organizations explained just 3% of variance of the variable criteria, not being meaningful its contribution. In summary, the present study demonstrated that the perception of an articulated purpose of the organization to create emotional bonds in a way to contribute to the well-being of their employees in terms of appreciation, free communication and participation in decision making, promote positive reports of WBW in the psychologists surveyed. They haven t found yet researches that contemplate the same theoretical model of investigation proposed. These study contributions shared can be used in people management in order to promote impacts in worker health as well in organization productivity.